Study of the Transformational Leadership and Organizational Culture as Predictors of Employee Creativity and Innovation in the Iraq Oil and Gas Service Industry - Firas Salman Khudhair; Rafiduraida Abdul Rahman; Ahmad Amri Bin Zainal Adnan; Dr. Anmar Adnan Khudhair (Zien Journals, 2022)
The 21st century global market demands highly skilled workforce who are intellectually active, creative, innovative and capable of critical thinking. Therefore, this study examines the factors determining employee creative and innovative undertakings at work in the oil and gas industry in Iraq with a focus on transformational leadership and organizational culture. The study adopted survey design and simple and moderatedregression analyses to test seven hypotheses. Data were collected from 414 (270 males and 144 females) randomly selected employees of four oil and gas service companies in Lagos aged between 19 and 61 years (x=32.4). Employees completed questionnaires consisting of validated scales of employee creativity and innovation, transformational leadership and organizational culture in the study. Cronbach alpha of the scales ranged from 0.86 to 0.96. Results showed that transformational leadership has significant impacton employee creativity (R²=.42, p <.001) and employee innovation (R2=.42, p><.001); organizational culture has significant impact on employee creativity (R²=.26, p><.001)and employee innovation (R2= .14, p><.001); and transformational leadership and organizational culture significantly interacted to impact employee creativity (ΔR²=.13, p><.001) and employee innovation (ΔR²=.14, p><.001). It was concluded that transformational leadership and appropriate organizational culture are important factors in facilitating employee creativity and innovation in the oil and gas service industry in Iraq . It was recommended that oil and gas service companies can facilitate employee creativity and innovation by promoting and investing in transformational leadership training of their managerial staff as well as instituting enabling innovative organisational culture.>
Keywords: Employee creativity; innovation; transformational leadership